Japan in the Heisei era (1989-2019) : multidisciplinary perspectives - Murai, Noriko; Kingston, Jeff, 1957-; Burrett, Tina (New York : Routledge Taylor & Francis Group, 2022)
"Japan in the Heisei Era (1989-2019) provides a retrospective and multidisciplinary account of a society in flux. Featuring analyses from leading scholars around the globe, this textbook examines the evolving contexts of Japan throughout the Heisei era and how longstanding verities and values are being called into question. Asking what this holds for future relations with the world and within its own communities, chapters delve into the layers of a complex and increasingly diverse society in the contexts of simmering ethnonationalism, economic torpor, political stagnation and cultural dynamics. Features in this textbook include: Analysis of key issues ranging from immigration, civil society, press freedom, politics, labour and the economy, diversity, the marginalization of women, Shinto, and Aum Shinrikyo Evaluation of the impact of Emperor Akihito on war memory, the imperial institution, art, regional relations and constitutional revision Multidisciplinary insights from both the social sciences and humanities Rich illustrations for visual analysis of developments in literature, film, art, and pop culture and what they reveal about contemporary Japan Providing students with dynamic analyses of how contemporary Japanese society continues to transform, this textbook will be essential reading for students of Japanese Studies, including Japanese culture, society, history and politics"--
Includes bibliographical references and index.
AAL
Keywords: Japan -- Economic conditions -- 1989-; Japan -- Social conditions -- 1989-; Japan -- Politics and government -- 1989-